The drug situation in Europe: an overview of data available on illicit drugs and new psychoactive substances from European monitoring in 2015. (30th September 2015) - Mounteney, Jane; Griffiths, Paul; Sedefov, Roumen; Noor, Andre; Vicente, Julián; Simon, Roland
Abstract: Aim: A central task for the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) is to produce an annual report of the latest data available on drug demand and drug supply in Europe. This paper is intended to facilitate a better understanding of, and easier access to, the main quantitative European level data sets available in 2015. Methods: The European reporting system formally covers all 28 European Union (EU) Member States, Norway and Turkey and incorporates multiple indicators alongside an early warning system (EWS) on uncontrolled new psychoactive substances (NPS). While epidemiological information is based largely on registries, surveys and other routine data reported annually, the EWS collects case‐based data on an ongoing basis. The 2015 reporting exercise is centred primarily on a set of standardized reporting tools. Results: The most recent data provided by European countries are presented, including data on drug use, drug‐related morbidity and mortality, treatment demand, drug markets and new psychoactive substances, with data tables provided and methodological information. A number of key results are highlighted for illustrative purposes. Drug prevalence estimates from national surveys since 2012 (last year prevalence of use among the 15–34 age band) range from 0.4% in Turkey to 22.1% in France for cannabis, from 0.2% in Greece and Romania to 4.2% in the United Kingdom for cocaine, from 0.1% in Italy and Turkey to 3% in the Czech Republic and the United Kingdom for ecstasy, and from 0.1% or less in Romania, Italy and Portugal to 2.5% in Estonia for amphetamine. Declining trends in new HIV detections among people who inject drugs are illustrated, in addition to presentation of a breakdown of NPS reported to the EU early warning system, which have risen exponentially from fewer than 20 a year between 2005 and 2008, to 101 reported in 2014. Conclusions: Structured information is now available on patterns and trends in drug consumption in Europe, which permits triangulation of data from different sources and consideration of methodological limitations. Opioid drugs continue to place a burden on the drug treatment system, although both new heroin entrants and injecting show declines. More than 450 new psychoactive substances are now monitored by the European early warning system with 31 new synthetic cathinones and 30 new synthetic cannabinoid receptor agonists notified in 2014.